The impact of social change on the position and relationship of teachers and students in teaching - Arsić, Zvezdan M.; Radojević, Tatjana S. (Sociološki pregled, 2019)
The last decade of the XX and the beginning of the XXI century of society in transition was marked by major social changes. These changes, which are characterized by the transformation from the traditional to the contemporary approach, lead to numerous changes in the educational and teaching theory and practice. The essence of the changes in the educational sphere is focused on the understanding of the connection between the development of society and education, the transformation of the system of education, as well as the examination of the position and relationship of teachers and students in teaching. Teaching is a social category in which the goals and tasks of upbringing and education are fulfilled in the most organized and systematic way, characterized by socio-historical conditionality and foundation. Acknowledging this fact, as well as the aforementioned findings and requirements, the primary focus of the paper is directed towards descriptivehistorical study and analysis of the impact of social changes on the position and relationship of teachers and students in teaching throughout the historical development of society, with special attention to the impact of current social change in this domain.
Keywords: social development; social change; education; student; teacher